Quality of bottled water: An Applied Study on Riyadh City - Al Mubarak, Hasaa Abdulaziz Abdulrahman; Al-Fayez, Reem Abdullah Saud (Journal of natural sciences, life and applied sciences, 2018)
The private sector established desalination facilities for sale and marketing of plastic water bottles in different sizes directly to the consumer in order to provide high quality water. As a result, bottled water has become increasingly popular. To understand the quality of water and its conformity with the international standards, a study was conducted on samples from twenty different factories that produce bottled water, it was found that the water under study is in conformity with the Saudi standards, the International Water Association standards and the Food and Drug Administration standards, except for turbidity that has exceeded the permissible level in AlQassim water, reaching 0.83 NTU. The study recommends attaching water properties to the bottles along with the water source, it also recommends creating an electronic database of the bottled water factories.